Mechanism of Growth Inhibition of Prostate Cancer Xenografts by Valproic Acid. (23rd August 2012) - Sidana, Abhinav; Wang, Muwen; Shabbeer, Shabana; Chowdhury, Wasim H.; Netto, George; Lupold, Shawn E.; Carducci, Michael; Rodriguez, Ronald
Abstract : Valproic Acid (VPA), a histone deacetylase inhibitor, has been demonstrated to cause a marked decrease in proliferation of prostate cancer (PCa) cells in vitro and a significant reduction in tumor volume in vivo . The goal of this study is to better understand the VPA-induced growth inhibition in vivo, by studying expression of various markers in PCa xenografts. Methods . For in vitro experiments, PCa cells were treated with 0, 0.6, and 1.2 mM VPA for 14 days. For in vivo models, experimental animals received 0.4% VPA in drinking water for 35 days. Tissue microarray was generated using cell pellets and excised xenografts. Results . VPA treatment causes cell cycle arrest in PCa cells in vivo, as determined by increase in p21 and p27 and decrease in cyclin D1 expression. Increased expression of cytokeratin18 was also seen in xenografts. LNCaP xenografts in treated animals had reduced androgen receptor (AR) expression. While decreased proliferation was found in vitro, increase in apoptosis was found to be the reason for decreased tumor growth in vivo . Also, an anti-angiogenic effect was observed after VPA treatment. Conclusion . VPA inhibits tumor growth by multiple mechanisms including cell cycle arrest, induction of differentiation, and inhibition of growth of tumor vasculature.